PENINGKATAN KREATIVITAS ANAK DESA SELAT DALAM MEMBUAT KERAJINAN TANGAN DARI SAMPAH PLASTIK MELALUI MEDIA PEMBELAJARAN BERBASIS VIDEO YOUTUBE - I Komang Angga Sila Dharma; I Nyoman Sudirman (LPPM Universitas Cipta Mandiri, 2024)
This research aims to explore the impact of implementing the Video-Based Learning Model on children's creativity and plastic waste management in Selat Village. This model is designed to provide an innovative approach to learning by utilizing video technology to teach children how to make crafts from plastic waste. The research method used is PALS (Participatory Action Learning System) with VBL (Video Based Learning) teaching. This research was carried out in KKN activities in Selat Village involving 35 children aged 9-12 years by creating small groups consisting of 4-6 children. The research results show that the application of the Video-Based Learning Model significantly increases the creativity of Selat Village children. Children are not only able to make creative handicrafts, but also experience positive changes in their perception of plastic waste. Even though there are several obstacles, this research is expected to make a positive contribution to the education and creativity of children in rural areas, as well as become the basis for learning innovation, and increase the creativity of rural children as a whole.